DETERMINAN MANAJEMEN PAJAK PADA PERUSAHAAN CONSUMER NON-CYCLICALS DI BEI 2021-2024 - Ti Tanawi, Valencia; Margareta Febe (Jurnal Akuntansi, 2026)
This study aims to examine the effect of profitability, leverage, fixed asset intensity, institutional ownership, and independent commissioners on tax management. The research gap underlying this study is based on the increasing number of tax interpretation disputes in the Tax Court, as well as inconsistencies in previous empirical findings regarding the effectiveness of corporate governance in mitigating overly aggressive tax management practices. This study is grounded in the importance of corporate efforts to manage tax burdens efficiently while complying with applicable tax regulations. The research employs a quantitative approach using secondary data obtained from the financial statements of consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The sample was selected using a purposive sampling method, resulting in 155 research observations. Data analysis was conducted using multiple linear regression analysis. The findings indicate that profitability, leverage, and fixed asset intensity have a positive and significant effect on tax management. Institutional ownership is found to have a negative and significant effect on tax management, while independent commissioners do not show a significant effect. This study contributes by focusing on the consumer non-cyclicals sector, which demonstrates high sensitivity to post-pandemic profit stability. The practical implications suggest that institutional monitoring mechanisms are effective instruments for controlling compliance, while tax authorities should strengthen supervision over corporate interest expenses and fixed asset depreciation practices.